Surface dose variations in 6 and 10 MV flattened and flattening filter‐free (FFF) photon beams - Cashmore, Jason (J Appl Clin Med Phys, 2016)
As the use of linear accelerators operating in flattening filter‐free (FFF) modes becomes more widespread, it is important to have an understanding of the surface doses delivered to patients with these beams. Flattening filter removal alters the beam quality and relative contributions of low‐energy X‐rays and contamination electrons in the beam. Having dosimetric data to describe the surface dose and buildup regions under a range of conditions for FFF beams is important if clinical decisions are to be made. An Elekta Synergy linac with standard MLCi head has been commissioned to run at 6 MV and 10 MV running with the flattening filter in or out. In this linac the 6 MV FFF beam has been energy‐matched to the clinical beam on the central axis ([Formula: see text]). The 10 MV beam energy has not been adjusted. The flattening filter in both cases is replaced by a thin (2 mm) stainless steel plate. A thin window parallel plate chamber has been used to measure a comprehensive set of surface dose data in these beams for variations in field size and SSD, and for the presence of attenuators (wedge, shadow tray, and treatment couch). Surface doses are generally higher in FFF beams for small field sizes and lower for large field sizes with a crossover at [Formula: see text] at 6 MV and [Formula: see text] at 10 MV. This trend is also seen in the presence of the wedge, shadow tray, and treatment couch. Only small differences ([Formula: see text]) are seen between the beams on varying SSD. At both 6 and 10 MV the filter‐free beams show far less variation with field size than conventional beams. By removing the flattening filter, a source of contamination electrons is exchanged for a source of low‐energy photons (as these are no longer attenuated). In practice these two components almost balance out. No significant effects on surface dose are expected by the introduction of FFF delivery. PACS number(s): 87.53.Bn, 87.55.ne, 87.56.bd